Flood Hazard Mapping Using Two Digital Elevation Models: Application in a Semi-Arid Environment of Morocco - Oumaima, Bennani; Yves, Tramblay; El Mehdi, Saidi Mohamed; Simon, Gascoin; Frederic, Leone (European Scientific Journal (Kocani), 2019)
The High Atlas of Morocco is a semi-arid mountainous environment that frequently suffers from natural hazards. For example, the watersheds upstream of Marrakech city are subject to extreme floods, caused by heavy rains. These episodes are frequent and often devastating, as was the August 1995 event that caused hundreds of deaths in the Ourika Valley. The purpose of this work is to characterize the risk of flooding in this valley, by simulating the water levels and the floodplain extension. This watershed of the Ourika is characterized by a high relief, a rugged topography and a low permeability substratum. To perform this hydraulic simulation, the resolution and accuracy of Digital Elevation Models (DEM) can strongly impact the results in terms of water levels and flow velocities during floods. Two digital elevation models (DEM) were compared : a DEM ASTER with a spatial resolution of 30 m and a DEM derived from stereoscopic images of Pleiades with a resolution of 4 m. Using a hydraulic model (HEC-RAS) and the two DEM resolutions, flood areas corresponding to different return periods are simulated and compared. For the assessment of the two DEM, many areas are selected that are characterized by different types of exposure : highly frequented tourist areas near a regional road and agricultural areas on alluvial terraces, where cultivated fields and infrastructure are vulnerable. The results showed that the high-resolution Pleiades DEM allows for accurate mapping of floodplains in complex terrain, as it realistically represents the topography and allows correct simulation of observed water levels. This study highlights the added value of a high-resolution remote sensing for flood modeling in areas where data are scarce.